L’Île rose et La Colonie de Charles Vildrac : le modèle utopique en question dans la littérature pour la jeunesse des années vingt - Martine Jacques (Strenae)
In 1924, an unpublished children’s text by Charles Vildrac, entitled L'Île rose, was published by Tolmer. It is about a utopia, sometimes verging on the Robinsonnade, which was then followed by La Colonie in 1930: these two texts provide a critical rewriting of the genre’s themes. Vildrac, a poet and dramatist up until that point, became a kind of privileged intercessor between the child and a real political imagination, which had embodied the narrative utopia since the 16th century. At the heart of the author’s poetic and political concern, the island-utopia theme in these two children’s novels was presented with talent and complexity. Fueled by a personal imagination that was very attached to the idea of utopia, these two novels revive and question archetypes of the genre, while critically reworking the utopian myth shaped by the previous generations. These illustrated stories fully participated in aesthetic, poetic and graphic innovations of the 1920s, as well as in ideological transformations which mark children’s literature during the interwar period.